2016
DOI: 10.26477/idj.v38i1.74
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Text Message Reminders on Oral Hygiene Compliance in Orthodontic Patients

Abstract: Objective: To determine if text message reminders regarding oral hygiene have an effect on maintaining good oral hygiene in orthodontic patients. Materials and Methods: In this randomized, controlled clinical trial, 34 orthodontic patients were assigned to a text message or control group. Patients in the text message group received 2 reminder text messages each week for 4 weeks and one reminder text message for 8 weeks thereafter. Oral hygiene compliance was measured using bleeding index (BI), modified gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
(27 reference statements)
0
17
0
2
Order By: Relevance
“…Eleven studies (Abdaljawwad, ; Alkadhi et al., ; Bowen, Rinchuse, Zullo, & DeMaria, ; Cozzani et al., ; Eppright et al., ; Hernández Albújar, ; Iqbal et al., ; Jadhav et al., ; Jejurikar, Nene, Kalia, Gupta, & Mirdehghan, ; Kumar et al., ; Li et al., ; Zotti et al., ) involved adolescents undergoing orthodontic treatment (Table ). Most of the studies that used text messaging combined two behaviour change techniques, that is, “Associations—prompts/cues” and “Natural consequences—information about health consequences” (Abdaljawwad, ; Bowen et al., ; Cozzani et al., ; Eppright et al., ; Hernández Albújar, ; Iqbal et al., ; Jadhav et al., ; Kumar et al., ). Among the three studies that used mobile application intervention, two of them employed different behaviour change techniques, “Comparison of behaviour—social comparison,” “Reward and threat—social reward” and “Comparison of outcomes—credible source” (Li et al., ; Zotti et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies (Abdaljawwad, ; Alkadhi et al., ; Bowen, Rinchuse, Zullo, & DeMaria, ; Cozzani et al., ; Eppright et al., ; Hernández Albújar, ; Iqbal et al., ; Jadhav et al., ; Jejurikar, Nene, Kalia, Gupta, & Mirdehghan, ; Kumar et al., ; Li et al., ; Zotti et al., ) involved adolescents undergoing orthodontic treatment (Table ). Most of the studies that used text messaging combined two behaviour change techniques, that is, “Associations—prompts/cues” and “Natural consequences—information about health consequences” (Abdaljawwad, ; Bowen et al., ; Cozzani et al., ; Eppright et al., ; Hernández Albújar, ; Iqbal et al., ; Jadhav et al., ; Kumar et al., ). Among the three studies that used mobile application intervention, two of them employed different behaviour change techniques, “Comparison of behaviour—social comparison,” “Reward and threat—social reward” and “Comparison of outcomes—credible source” (Li et al., ; Zotti et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (Abdaljawwad, ; Bowen et al., ; Cozzani et al., ; Eppright et al., ; Hashemian et al., ; Hernández Albújar, ; Iqbal et al., ; Jadhav et al., ; Jejurikar et al., ; Kumar et al., ; Makvandi et al., ; Sharma et al., ) used text messages to evaluate the improvement in oral health conditions, and three studies (Alkadhi et al., ; Li et al., ; Zotti et al., ) used mobile applications.…”
Section: Resultsmentioning
confidence: 99%
“…The current results were in agreement with those of studies that reported the positive e cacy of message reminders for oral hygiene promotion of patients during xed orthodontic treatment. [20][21][22][23] Evidence shows that dental caries following orthodontic treatment can negatively affect the patients' perception of orthodontic treatment, which would negatively impact the future attendance of patients. 20 Although initial enamel lesions may develop within 2-3 weeks following microbial plaque accumulation on tooth surfaces, 31 the current study did not show any signi cant change in caries index in the two groups during the 6-month course of treatment and the two groups were the same in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The increased patient cooperation achieved in this study also is consistent with the results of research regarding oral hygiene and plaque reduction. 8,[17][18][19][20][21][22][23][24] In those studies, patients who received messages via short message service or WhatsApp or who received calls from professionals exhibited better plaque control and a better hygiene score than patients in control groups who did not receive such notifications. This demonstrates that sending text messages is an effective method for improving oral hygiene in orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%